PEO-PAN-PEO sandwich structure composite solid electrolyte membrane, preparation method thereof and all-solid-state battery

By using the PEO-PAN-PEO sandwich structure composite solid electrolyte membrane in solid-state batteries, the problems of low mechanical strength and narrow electrochemical window of PEO matrix composite electrolyte are solved, and higher mechanical strength and electrochemical performance are achieved. The electrochemical window has been broadened and the performance of all-solid-state batteries has been improved.

CN119208723AActive Publication Date: 2024-12-27GUANGDONG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411341039.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing PEO-based composite solid electrolyte has low mechanical strength, large interface resistance and narrow electrochemical window, which leads to problems in dendrite growth and high-voltage cathode material matching, limiting its application prospects.

Method used

The preparation method of PEO-PAN-PEO sandwich structure composite solid electrolyte membrane is used. By mixing dopamine-modified inorganic filler and PEO powder in a mortar, a lithium salt solution is formed, and the PEO suspension is cast on both sides of the PAN nanofiber to form a sandwich. Structural composite membrane to improve mechanical strength and electrochemical window.

Benefits of technology

It significantly improves the mechanical strength and electrochemical window of PEO-based composite solid electrolytes, reduces the interface resistance, accelerates the electrochemical reaction kinetics of solid-state batteries, and improves the electrochemical performance of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208723A_ABST
    Figure CN119208723A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid electrolyte preparation, and particularly relates to a PAN-PEO-PAN sandwich structure composite solid electrolyte membrane, a preparation method thereof and a solid-state battery. The sandwich structure composite electrolyte membrane is composed of PEO layers on the upper side and the lower side and a PAN layer in the middle. The preparation method comprises the following steps: uniformly mixing a dopamine modified inorganic filler and PEO powder in a mortar; adding a lithium salt into an acetonitrile solvent, mixing to form a uniform solution, then adding the obtained mixture into the lithium salt uniform solution, and continuously stirring until the mixture is uniform to obtain a PEO suspension; and casting the PEO suspension on two sides of the PAN nanofiber skeleton, and drying completely to remove the organic solvent to obtain the PEO-PAN-PEO sandwich structure composite solid electrolyte membrane. According to the technical scheme provided by the invention, the lithium affinity of the PEO layer is reduced, the interface resistance of the solid-state battery is reduced, the solid-solid transmission reaction kinetics is accelerated, the PAN nanofiber layer endows the electrolyte membrane with higher mechanical strength, meanwhile, a 3D lithium ion transmission channel is provided for accelerating ion transmission, and the assembled all-solid-state battery shows excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolyte preparation, and in particular relates to a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane and a preparation method thereof and a solid-state battery. Background Art

[0002] Lithium metal batteries have attracted widespread attention due to their high theoretical specific capacity (3860mAh g-1) and energy density. However, the use of flammable and volatile organic liquid electrolytes in traditional lithium metal batteries has seriously hindered their practical application due to uncontrollable growth of dendrites, unstable electrolyte / Li interface and poor cycle stability.

[0003] As a potential substitute for liquid organic electrolytes, solid electrolytes have potential advantages in safety and dendrite inhibition, and are expected to give full play to the advantages of high specific energy of metal lithium negative electrode. Among them, PEO / ceramic composite solid electrolytes have received extensive attention in solid-state lithium metal batteries due to the advantages of PEO's high Li+ solubility, flexibility, processability, low cost, and synergistic ceramic electrolytes. Polymer solid electrolytes are flexible, low-cost and easy to process, but their room temperature conductivity is usually low; inorganic solid electrolytes have high room temperature conductivity, but their preparation process is complex, costly, and their high hardness leads to poor compatibility with the electrode interface. The development of organic-inorganic composite solid electrolytes can effectively combine the advantages of both, so it is considered to be one of the materials with the most promising large-scale practical applications. Researchers have proposed a variety of effective strategies for the design of composite solid electrolyte structures, mainly including low-dimensional inorganic filler modification, three-dimensional inorganic filler modification, and electrolyte multilayer composites.

[0004] However, the further development of solid-state electrolytes is hampered by problems such as insufficient mechanical strength to resist the growth of dendrites during battery operation, which can cause the electrolyte membrane to pierce and lead to battery failure, and a narrow electrochemical window that cannot match high-voltage cathode materials.

[0005] Therefore, the PEO-PAN-PEO sandwich structure composite solid electrolyte was designed through the electrospinning / casting strategy, which effectively enhanced the mechanical strength of the electrolyte membrane, broadened the electrochemical window, and reduced the interfacial resistance, thereby enhancing the solid-solid transport reaction kinetics. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the existing PEO-based composite solid electrolytes, such as low mechanical strength, large interface resistance and narrow electrochemical window, and to provide a PEO-based composite solid electrolyte membrane with high mechanical strength and wide electrochemical window.

[0007] Another object of the present invention is to provide a method for preparing a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane.

[0008] Another object of the present invention is to provide a PEO-PAN-PEO sandwich structure composite solid electrolyte for use in an all-solid-state battery.

[0009] The above-mentioned purpose of the present invention, the first technical solution provided by the present invention is as follows:

[0010] 1) mixing the dopamine-modified inorganic filler and the PEO powder in a mortar in a mass ratio of 0.007-0.07:0.2-1.0 to obtain a mixture;

[0011] 2) Add lithium salt into an organic solvent and mix to form a uniform lithium salt solution; the concentration of the solution is 0.02 mol / L-0.36 mol / L.

[0012] 3) adding the mixture obtained in step 1) to the lithium salt solution in step 2) and continuing to stir until uniform to obtain a PEO suspension;

[0013] In step 3), the mass ratio of PEO to lithium salt is 0.2-1.0:0.1-0.5;

[0014] 4) dissolving the ceramic nanoparticles and PAN powder in a DMF solvent at a mass ratio of 0.026-0.5:0.5-2.0, and stirring to obtain a spinning suspension;

[0015] 5) electrospinning the spinning suspension obtained in step 4) on a spinning machine to obtain PAN nanofibers;

[0016] 6) Casting the suspension obtained in step 3) on both sides of the PAN nanofibers obtained in step 5), and obtaining a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane after drying.

[0017] Furthermore, in the above-mentioned method for preparing the PEO suspension, the organic solvent is acetonitrile.

[0018] Furthermore, in the above-mentioned method for preparing the PEO suspension, the concentration of the lithium salt solution is 0.3-1.8 mmol.

[0019] Furthermore, in the above-mentioned method for preparing PEO suspension, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium difluorooxalate borate, and lithium bis(fluorosulfonyl)imide.

[0020] Furthermore, in the above-mentioned method for preparing the PEO-PAN-PEO sandwich structure composite solid electrolyte membrane, the drying is performed at 60° C. for 24 hours.

[0021] Furthermore, in the above-mentioned method for preparing the PEO-PAN-PEO sandwich structure composite solid electrolyte membrane, the dopamine-modified inorganic filler is prepared by the following method:

[0022] 1) dissolving dopamine hydrochloride in deionized water and stirring magnetically until it is completely dissolved to obtain a dopamine solution;

[0023] 2) dissolving tris(hydroxymethyl)aminomethane in deionized water, adding no filler after it is completely dissolved, and performing magnetic stirring to form a mixed solution;

[0024] 3) slowly dropping the dopamine solution prepared in step 2) into the mixed solution in step 1), stirring at room temperature, then centrifuging and washing, and drying the washed solid to obtain a dopamine-modified inorganic filler.

[0025] The mass ratio of dopamine hydrochloride, tris(hydroxymethyl)aminomethane, and inorganic filler is: 0.1-0.5: 0.1-0.2: 0.1-0.8

[0026] Furthermore, in the above-mentioned method for preparing the PEO-PAN-PEO sandwich structure composite solid electrolyte membrane, the inorganic filler is Al 2 O 3 、TiO 2 、CeO 2 One or more of .

[0027] Furthermore, in the above-mentioned method for preparing the PEO-PAN-PEO sandwich structure composite solid electrolyte membrane, the electrospinning voltage range of the spinning machine is 12-20 kV.

[0028] Furthermore, in the above-mentioned method for preparing the PEO-PAN-PEO sandwich structure composite solid electrolyte membrane, the ceramic nanoparticles are one or more of LATP, LLZTO, LLTO, and LLZO.

[0029] The second technical solution provided by the present invention is a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane, which is prepared by the method described in the first technical solution; the sandwich structure composite electrolyte membrane consists of upper and lower PEO layers and a middle PAN layer.

[0030] The third technical solution provided by the present invention is an all-solid-state battery, comprising the PEO-PAN-PEO sandwich structure composite solid electrolyte membrane described in the second technical solution.

[0031] The present invention has the following beneficial effects:

[0032] 1. The PEO-PAN-PEO sandwich structure composite solid electrolyte membrane provided by the present invention greatly improves the mechanical strength of the PEO-based composite solid electrolyte and broadens the electrochemical window, thereby improving the electrochemical performance of the all-solid-state battery.

[0033] 2. The technical solution provided by the present invention has a lithium affinity of the PEO layer, which reduces the interfacial resistance of the solid-state battery and accelerates the kinetics of the solid-solid transfer reaction. The PAN nanofiber layer gives the electrolyte membrane higher mechanical strength and provides a 3D lithium ion transmission channel to accelerate ion transmission. The assembled all-solid-state battery exhibits excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a structural diagram of a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane according to an embodiment of the present invention.

[0035] Figure 2 It is a graph showing the tensile-stress test results of the embodiments of the present invention and the comparative examples.

[0036] Figure 3 1 and 2 are LSV diagrams of the embodiments of the present invention and the comparative examples.

[0037] Figure 4 Graph showing the electrochemical performance of the all-solid-state battery of the present invention. DETAILED DESCRIPTION

[0038] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0039] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0040] Example 1

[0041] The preparation steps of the PEO-PAN-PEO sandwich structure composite solid electrolyte membrane provided in this embodiment are as follows:

[0042] S1: Preparation of dopamine modified inorganic filler:

[0043] Measure 12 ml of deionized water in a beaker, weigh 0.5 g of dopamine hydrochloride and stir for 5 minutes to form a uniform solution A. Measure 100 ml of deionized water in a beaker, weigh 0.1214 g of tris(hydroxymethyl)aminomethane) and add it to the beaker and stir for 15 minutes, then add 0.5 g of nano-alumina and continue stirring for 15 minutes to form a uniform solution B. After that, slowly add solution A to solution B while stirring to form solution C. After sealing solution C with plastic wrap, place it at room temperature and stir it magnetically for 24 hours, and solution C gradually turns black. After centrifuging and washing solution C (washing with ultrapure water 5 times, then washing twice with ethanol), the solid matter is dried (70°C, 72 hours) to obtain dopamine-modified alumina (Al 2 O 3 @PDA).

[0044] S2: Preparation of PEO suspension:

[0045] Accurately weigh 0.2g of LiTFSI (lithium bis(trifluoromethanesulfonyl imide) powder in a glass bottle, add 8ml of acetonitrile, and stir magnetically to obtain a uniform solution A. Weigh 0.5g of PEO (polyethylene oxide, molecular weight 600,000) powder and 0.037g of Al 2 O 3 PDA was ground and mixed in an agate mortar for 15 min to obtain a mixture B. The mixture B was added to the homogeneous solution A, magnetically stirred for 12 hours, ultrasonicated for 2 hours, and allowed to stand for 6 hours to obtain a PEO suspension.

[0046] S3: Preparation of PAN spinning solution:

[0047] Accurately weigh 0.9 g of PAN powder and 0.1 g of LLTO (lithium lanthanum titanium oxide ceramic nanoparticles) into a glass bottle, and add 10 ml of N,N-dimethylformamide (DMF) at the same time, and stir magnetically to obtain a PAN spinning solution with a ceramic nanoparticle content of 10%.

[0048] S4: Preparation of PAN nanofibers:

[0049] The PAN spinning solution obtained in step S3 is electrospun in a spinning machine using a voltage of 12-20 kV to obtain PAN nanofibers.

[0050] S5: Preparation of PEO-PAN-PEO sandwich structure composite solid electrolyte membrane:

[0051] In a glove box, the PEO suspension obtained from S2 was first cast on one side of the PAN nanofiber and then allowed to stand in the glove box for 6 hours to allow the solvent to evaporate. The PEO suspension was then cast on the other side of the PAN nanofiber. After the solvent evaporated initially at room temperature, it was transferred to a vacuum oven and dried at 60°C for 24 hours to completely remove the solvent, thereby obtaining a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane. The structure diagram is shown in Figure 1 .

[0052] Example 2

[0053] The mass of PAN in step S3 of Example 1 was adjusted to 0.95 g, the mass of LLTO was adjusted to 0.05 g, and the other steps were the same as in Example 1.

[0054] Example 3

[0055] The mass of PAN in step S3 of Example 1 was adjusted to 0.8 g, the mass of LLTO was adjusted to 0.2 g, and the other steps were the same as in Example 1.

[0056] Example 4

[0057] The LLTO in step S3 of Example 1 is adjusted to LATP (lithium aluminum titanium phosphate), and the other steps are consistent with Example 1.

[0058] Example 5

[0059] The LLTO in step S3 of Example 1 is adjusted to LLZO (lithium lanthanum zirconium oxide), and the other steps are consistent with Example 1.

[0060] Comparative Example 1

[0061] By EO:Li + Weigh 0.2 g of LiTFSI powder in a glass bottle with a molar ratio of 16:1, add 8 ml of acetonitrile, and stir magnetically to obtain a uniform solution A. Weigh 0.5 g of PEO (molecular weight 600,000) powder and 0.037 g of Al 2 O 3 @PDA was ground and mixed in an agate mortar for 15 minutes to obtain a mixture B. Mixture B was added to the uniform solution A and magnetically stirred for 12 hours, then ultrasonicated and allowed to stand for 6 hours to obtain a casting solution. The casting solution obtained above was poured into a silica gel mold with an inner diameter of 50mm×50mm×5mm. After the acetonitrile solvent was naturally evaporated at room temperature for 12 hours to form a film, it was transferred to a vacuum oven and dried at 60°C for 24 hours to completely remove the acetonitrile, thereby obtaining a single-layer PEO composite solid electrolyte membrane.

[0062] Comparative Example 2

[0063] By EO:Li +Weigh 0.2 g of LiTFSI powder in a glass bottle with a molar ratio of 16:1, add 8 ml of acetonitrile, and stir magnetically to obtain a uniform solution A. Weigh 0.5 g of PEO (molecular weight 600,000) powder and 0.037 g of Al 2 O 3 Grind and mix in an agate mortar for 15 minutes to obtain a mixture B. Add the mixture B to the uniform solution A, stir magnetically for 12 hours, ultrasonicate, and stand for 6 hours to obtain a casting solution. Pour the casting solution obtained above into a silica gel mold with an inner diameter of 50mm×50mm×5mm, wait for the acetonitrile solvent to evaporate naturally for 12 hours at room temperature to form a film, and then transfer it to a vacuum oven at 60°C and dry it for 24 hours to completely remove the acetonitrile, thereby obtaining a single-layer PEO composite solid electrolyte membrane.

[0064] Comparative Example 3

[0065] By EO:Li + Accurately weigh 0.2g of LiTFSI powder in a glass bottle with a molar ratio of 16:1, add 8ml of acetonitrile, and stir evenly with a magnetic stirrer to obtain a uniform solution A. Weigh 0.5g of PEO (molecular weight 600,000) powder and add it to the uniform solution A. Stir it magnetically for 12 hours, then ultrasonicate it and let it stand for 6 hours to obtain a casting liquid. Pour the casting liquid obtained above into a silica gel mold with an inner diameter of 50mm×50mm×5mm. After the acetonitrile solvent evaporates naturally for 12 hours at room temperature to form a film, transfer it to a vacuum oven and dry it at 60°C for 24 hours to completely remove the acetonitrile, and obtain a single-layer PEO composite solid electrolyte membrane.

[0066] Experimental Example 1: The present invention uses the PEO composite solid electrolyte to prepare a performance test of an all-solid-state battery.

[0067] The PEO composite solid electrolyte membrane obtained in Example 1 was assembled into a CR2032 button cell according to conventional operations in the art.

[0068] Preparation of positive electrode sheet: lithium iron phosphate material, superP conductive agent and PVDF were mixed evenly in a mass ratio of 8:2:1, N-methylpyrrolidone (NMP) was added to prepare a slurry, which was coated on aluminum foil to prepare a positive electrode sheet, and then vacuum dried and cut into discs with a diameter of 13 mm. The above-prepared electrode sheets formed a CR2023 button battery.

[0069] The battery was tested for charge and discharge performance at a voltage range of 2.8-4.0V using a Xinwei charge and discharge tester. The long cycle performance of the all-solid-state lithium metal battery prepared from the PEO composite solid electrolyte membrane obtained in Examples 1-5 and Comparative Examples 1-3 was tested at a rate of 0.5C; the linear cyclic voltammetry (LSV) curve test was performed on the button battery prepared from the PEO-based composite solid electrolyte membrane obtained in the Examples and Comparative Examples. The results are as follows: Figure 3-4shown.

[0070] from Figure 3 It can be seen that the electrochemical window of Example 1 reaches 5.1V, and the electrochemical windows of Examples 2 and 3 also reach 4.75V and 4.8V; while the electrochemical window of Comparative Example 1 is only 4.6V; this indicates that the designed PEO-PAN-PEO sandwich structure composite solid electrolyte effectively broadens the electrochemical window of the PEO composite solid electrolyte.

[0071] from Figure 4 It can be seen that the composite solid electrolyte prepared in Example 1 has a first cycle discharge capacity of 168.8 mAh g at 0.5 C. -1 ; After 400 cycles, the discharge capacity is 131.2 mAh g -1 ; The capacity retention rate is 77.7%; The first cycle discharge capacity of the composite solid electrolyte prepared in Example 2 at 0.5C is 166.6 mAh g -1 ; After 337 cycles, the discharge capacity is 126.3 mAh g -1 ; The capacity retention rate is 75.8%; The composite solid electrolyte prepared in Example 3 has a first cycle discharge capacity of 157.13 mAh g at 0.5C -1 ; After 400 cycles, the discharge capacity is 110.1 mAh g -1 ; The capacity retention rate is 70.1%; The composite solid electrolyte prepared in Example 4 has a first cycle discharge capacity of 168.5 mAh g at 0.5C -1 ; After 294 cycles, the discharge capacity is 131.7 mAh g -1 ; The capacity retention rate is 78.1%; The composite solid electrolyte prepared in Example 5 has a first cycle discharge capacity of 152.2 mAh g at 0.5C -1 ; After 400 cycles, the discharge capacity is 110.8 mAh g -1 ; The capacity retention rate is 72.8%; The composite solid electrolyte prepared in Comparative Example 1 has a first cycle discharge capacity of 151.3 mAh g at 0.5C -1 ; After 328 cycles, the discharge capacity is 98.2 mAh g -1 ; The capacity retention rate is 64.9%; The composite solid electrolyte prepared in Comparative Example 2 has a first cycle discharge capacity of 142.9 mAh g at 0.5C -1 ; After 181 cycles, the discharge capacity is 123.9 mAh g -1 ; The capacity retention rate is 86.7%; The composite solid electrolyte prepared in Comparative Example 3 has a first cycle discharge capacity of 131.3 mAh g at 0.5C -1 ; After 303 cycles, the discharge capacity is 63.2 mAh g-1 ; The capacity retention rate is 48.1%; This indicates that the prepared PEO composite solid electrolyte has a higher discharge specific capacity, a lower capacity attenuation rate and better long-cycle stability.

[0072] The tensile-stress test can reflect the mechanical strength of the electrolyte membrane. Figure 2 The stress-strain curve shows that the mechanical toughness of Example 1 is the largest, and its tensile strength can reach 2.06Mpa. At the same time, the tensile strengths of Examples 2 and 3 are 1.64Mpa and 1.28Mpa, respectively. In comparison, Comparative Examples 1-3 have lower tensile strengths, which are 0.71Mpa, 0.173Mpa and 0.123Mpa, respectively. This shows that the designed PEO-PAN-PEO sandwich structure composite solid electrolyte membrane further enhances the mechanical properties.

[0073] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a PAN-PEO-PAN sandwich structure composite solid electrolyte membrane, characterized in that: The following steps are included in sequence: 1) mixing the dopamine-modified inorganic filler and the PEO powder in a mortar in a mass ratio of 0.007-0.07:0.2-1.0 to obtain a mixture; 2) adding lithium salt into an organic solvent and mixing to form a uniform lithium salt solution; 3) adding the mixture obtained in step 1) to the lithium salt solution in step 2) and continuing to stir until uniform to obtain a PEO suspension; In step 3), the mass ratio of PEO to lithium salt is 0.2-1.0:0.1-0.5; 4) dissolving ceramic nanoparticles and PAN powder in a solvent at a mass ratio of 0.026-0.5:0.5-2.0, and stirring to obtain a spinning suspension; 5) electrospinning the spinning suspension obtained in step 4) in a spinning machine to obtain PAN nanofibers; 6) Casting the suspension obtained in step 3) on both sides of the PAN nanofibers obtained in step 5), and obtaining a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane after drying.

2. The method for preparing a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane according to claim 1, characterized in that: The organic solvent in step 2) is acetonitrile, and the solvent in step 4) is N,N-dimethylformamide.

3. The method for preparing a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane according to claim 1, characterized in that: The lithium salt described in step 2) is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium difluorooxalatoborate, and lithium bis(fluorosulfonyl)imide; the ceramic nanoparticles described in step 4) are one or more of LATP, LLZTO, LLTO, and LLZO.

4. The method for preparing a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane according to claim 1, characterized in that: The concentration of the lithium salt solution is 0.02mol / L-0.36mol / L.

5. The method for preparing a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane according to claim 1, characterized in that: The drying in step 6) is carried out at 60° C. for 24 hours; the voltage of the spinning machine during the electrospinning is 12-20 kV.

6. The method for preparing a PEO-based composite solid electrolyte membrane according to claim 1, characterized in that: The dopamine-modified inorganic filler is prepared by the following method: 1) dissolving dopamine hydrochloride in deionized water and stirring magnetically until it is completely dissolved to obtain a dopamine solution; 2) dissolving tris(hydroxymethyl)aminomethane in deionized water, adding no filler after it is completely dissolved, and performing magnetic stirring to form a mixed solution; 3) slowly dropping the dopamine solution prepared in step 2) into the mixed solution in step 1), stirring at room temperature, then centrifuging and washing, and drying the washed solid to obtain a dopamine-modified inorganic filler; The mass ratio of dopamine hydrochloride, tris(hydroxymethyl)aminomethane and inorganic filler is 0.1-0.5: 0.1-0.2: 0.1-0.8g.

7. The method for preparing a PEO-PAN-PEO sandwich structure composite solid electrolyte membrane according to claim 6, characterized in that: The inorganic filler is one or more of Al2O3, TiO2, and CeO2.

8. A PEO-PAN-PEO sandwich structure composite solid electrolyte membrane, characterized in that: Prepared by the method described in any one of claims 1 to 7.

9. The PEO-PAN-PEO sandwich structure composite solid electrolyte membrane according to claim, characterized in that: The sandwich structure composite electrolyte membrane consists of upper and lower PEO layers and a middle PAN layer.

10. An all-solid-state battery, characterized in that: It includes the PEO-PAN-PEO sandwich structure composite solid electrolyte membrane as described in claim 8.

Citation Information

Patent Citations

  • Organic silicon modified PA6 / PAN nanofiber membrane composite solid electrolyte and preparation method thereof

    CN116505069A

  • Composite solid electrolyte membrane and preparation method and application thereof

    CN116914234A

  • PEO-based composite electrolyte membrane, preparation method thereof and all-solid-state battery

    CN118136944A

  • Fabricating mehtod of solid electrolyte

    KR1020170084912A